Lora-Based Internet Of Things (Iot) Wireless Network System To Monitor Covid-19 Patients - Muzafar, Muhammad Izz Zharfan Azhar (Universiti Sains Malaysia, 2021)
The implementation of Internet of Things (IoT) in the medical field using Long Range (LoRa) technology is the key area of interest in this project. LoRa has the ability to transmit packets of data across great distances, has low power consumption, and high immunity to interference compared to other Low-Power Wide-Area (LPWA) technologies. The emergency situation for COVID-19 patients who have severe symptoms can be detected and diagnosed more efficiently by the medical staff because this LoRa LPWA technology provides an efficient, flexible, and cost-effective solution to real-world problems in urban, rural, and indoor use cases. The patients’ blood oxygen saturation and pulse rate are measured via MH-ET Live MAX30102 sensor. This sensor has the advantage of being compatible with the Arduino board, specifically Arduino Uno which is based on ATmega328P. The sensor is then integrated with TTGO LoRa SX1276 modules of the Wireless Sensor Network. In this project, peer-to-peer LoRa communication is implemented, which covers the physical layer of the LoRa communication protocol where the transmitter and receiver communicates directly without the central server or gateway. After integrating the sensor to LoRa transmitter, the data are sent to the receiver, which the receiver is connected to Arduino IDE software to evaluate the sensor output. From the result, user must be in rested condition, place their fingertip onto the sensor properly for a few moments without any movement, and use body part of fingertip only in order to obtain an accurate readings. However, the measured pulse rate or oxygen saturation might be inaccurate of either numbers due to incompatible codes used or hardware defects with elevated value of heart rate 166 and 214 beats per minute recorded. Furthermore, this project evaluates the LoRa SX1276 transceiver module on outdoor environment at suburban area in Nibong Tebal with specific parameters that has been programmed. Line-of-sight (LOS) test shows that the maximum displacement between the modules are 1300 meters with limitation of received signal strength indicator (RSSI). The signal-to-noise ratio (SNR) and RSSI recorded at 1300 meters distance is -6.5dB and -118dBm respectively. Non-line-of-sight (NLOS) test shows that LoRa still able to communicate with each other after 8 blocks of houses with an approximate displacement of 240 meters apart between the modules, with each house has approximately 30 meters length. With the presence of other radio frequency devices that act as noise in the residential suburban area, LoRa modules are still able to communicate with RSSI and SNR value of -113dBm and -5.42dB respectively after being obstructed by 8 blocks of houses. Then, parameters of LoRa SX1276 module is calculated by using LoRa Modem Calculator Tool to analyse the theoretical performances and effectiveness of LoRa communications such as sensitivity, link budget, bit rate, time on air and symbol time by varying the spreading factor, bandwidth and coding rate. In the analysis, all these LoRa performance parameters shows various patterns of graphs because spreading factor, bandwidth and coding rate are the main input parameters that affects LoRa signal modulation and demodulation properties.